If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(h + 3) + -3(h + -5) = 16 Reorder the terms: 4(3 + h) + -3(h + -5) = 16 (3 * 4 + h * 4) + -3(h + -5) = 16 (12 + 4h) + -3(h + -5) = 16 Reorder the terms: 12 + 4h + -3(-5 + h) = 16 12 + 4h + (-5 * -3 + h * -3) = 16 12 + 4h + (15 + -3h) = 16 Reorder the terms: 12 + 15 + 4h + -3h = 16 Combine like terms: 12 + 15 = 27 27 + 4h + -3h = 16 Combine like terms: 4h + -3h = 1h 27 + 1h = 16 Solving 27 + 1h = 16 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-27' to each side of the equation. 27 + -27 + 1h = 16 + -27 Combine like terms: 27 + -27 = 0 0 + 1h = 16 + -27 1h = 16 + -27 Combine like terms: 16 + -27 = -11 1h = -11 Divide each side by '1'. h = -11 Simplifying h = -11
| -90=-5(8+2n) | | y-8=-5/7x | | 5.5-5x= | | 14x=5x+990 | | (2n-14)(n-5)=90 | | -20+n=-18 | | 5x+11=-48 | | (2x-4)(x+1)=(x-3)(x-2) | | 1/2(x)(4x)=50 | | 1/4*-16 | | -7/6=v/12 | | 0.2x-0.5(2x-1)=-0.3(x+4) | | 0.33x+7+x=19 | | 3h+41=h | | 15x-18=6y | | x(x+6)=12 | | 17+6x=1+x | | -26=v-12 | | 5x+21=10x+19 | | 3x+2+x=.333(12x+6) | | y+y*4=16 | | 169x^2-182x-61=0 | | 3y+7-y=-2y+3-3y+13 | | 5x+3=-7x+11 | | 162=102-x | | 11x-2x^2-4=11x+4 | | 53-v=184 | | 7cos(x)=x+1 | | 8=13y+2 | | 1/X1/3 | | -5m+4=11 | | (X+4)(3-x)(2x-1)=0 |